Technical Planning Analysis of the Garut-Tasikmalaya-Cilacap Toll Road Section I (Gedebage Station 0+000 – North Garut Station 45+200) - Styadi, Kiky Bagas; Akbardin, Juang; Sekaryadi, Yudi (PT FORMOSA CENDEKIA GLOBAL, 2025)
Population growth and economic activity in West Java and Central Java increase traffic volume and congestion, especially in the southern lanes that do not have toll roads. The distribution of goods and people's mobility still rely on arterial roads such as Jalan Nagreg which is narrow and prone to congestion. This study aims to analyze the planning of the Gedebage-Tasikmalaya-Cilacap Toll Road Section I of the Gedebage-North Garut section with a quantitative descriptive method. The results show segments 1–6 are heavy traffic, while segments 7–10 are smooth. Trase 2 was chosen because it was more optimal in terms of technical, cost, and environmental aspects. The planning includes 41 PIs, 79 PVIs, three main interchanges, as well as the construction of 300 mm JRCP pavement, 150 mm thin concrete, 200 mm class A concrete, and 200 mm optional stacks.